A study to assess the effectiveness of self-instruction module on knowledge among adolescents regarding substance abuse in selected school of Raigad - Sudershna Prasad, Mrs (International Journal of Nursing Research, 2023)
Introduction: Adolescents are “biologically wired” to seek new experiences and take risks, as well as to carve out their own identity. Trying drugs may fulfil all of these normal developmental drives, but in an unhealthy way that can have very serious long-term consequences. Tobacco, alcohols are the first addictive substances most adolescence try. Methodology: Total fifty (50) Subjects were taken in the study. Age group of these students was assessed between 13-16 years. Subjects enrolled according to inclusion and exclusion criteria. Sampling technique is the name or other identification of the specific process by which the entities of the sample have been selected. We have used nonprobability convenient sampling. The sample were selected the investigator approached the consent of concerned authority. A self-structured module was prepared and used for the data collection; questionnaire is a quick and generally inexpensive means of obtaining data from respondents. The self structured module was administered by the investigator. The duration of data collection was 10 minutes from each sample. Study instrument used by the researcher consisted of Demographic Questionnaire, Knowledge Questionnaire regarding Alcohol, Knowledge Questionnaire regarding Tobacco. Results: In our study major findings out of 50 samples, 29(58%) were boys and 21 (42%) were girls in the study. The students in age group 13-14 yrs were 38 (76%) and 15-16 yrs were 12 (24%).Maximum 78% of students are Hindu and least are Christian and others with 4% each and Muslims are 7%. Most of the parents have secondary education. Comparatively fathers are more educated than mothers and no mother is graduated. Maximum monthly income is <5,000 of the families. Maximum Alcohol consumption is by fathers (11) and maximum Tobacco consumption is by self. Maximum 90% are non consumers and 10% are consumers of tobacco in the samples. Maximum 92% are non consumers and 8% are consumers of alcohol. The mean value of pre-test knowledge was 21.46 and post test knowledge was 43.46 and also check the difference between pre and post test knowledge was 1.645 Conclusion: Studies have made it clear that drug education and prevention aimed at children and adolescents offers the best chance to curb abuse nationally